PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DESA DI DESA HATETABAKO KECAMATAN WASILE TENGAH KABUPATEN HALMAHERA TIMUR - Ngongare, Allen; ROMPAS, WELSON; KIYAI, BURHANUDDIN (Sam Ratulangi University, 2019)
The research objective was to explain in village development. In Hatetabako Village,Wasile sub-district, Central East Halmahera District. This study used a descriptive and repressive. Village secretary, head of BPD member (BPD),Community.data Collections uses interview guidelines,Documentation study observations while analysis techniques are carried out through the stages of data collection in development in the village of hatetabako Wasile SUB-District,central East Halmahera Regency,it was observed that the two criteria,nameli preventive and repressive,had not been maximally implemented. The village level needs to be improved through community participation in village development. Community invilopment in community participation in development is increased so that there are no misunderstandings between the village government and the communty, others are regulated in government regulation number 124 of 2001 concerning community participation in development villages,and the 2004 6 year law on villages,should be optimizedKey words: Community participation in village development